Components of Unrealistic Optimism of College Students: The Case of the COVID-19 Pandemic - Eshel, Yohanan; Kimhi, Shaul; Marciano, Hadas; Adini, Bruria (Frontiers in Psychology, 2021)
College students are among the most strongly affected populations by the COVID-19 pandemic, due to uncertainty regarding academic success, future careers, and social life during their study period. Their mental health and behavior may dramatically be impacted. The study examined an unrealistic optimism of Israeli college students in assessing the health, security and economic risks along the pandemic; and the contributions of these perceived risks to predicting psychological coping responses such as well-being, and coping suppressing response of anxiety, expressed during this pandemic. Using social networks, a questionnaire was disseminated to students during the third lockdown that was implemented in Israel during the pandemic. Depressive and anxiety symptoms; perceived threats; resilience; well-being; hope; and morale were measured, using a structured quantitative questionnaire. We hypothesized first, that these three perceived risks would be inversely rated, so that perceived health risk would be rated lowest, and perceived economic risk would be rated highest. A second and third hypotheses claimed that psychological coping responses articulated along this pandemic would be predicted by all these perceived risks, as well as observance of the pandemic precaution rules. A fourth hypothesis suggested that the three investigated perceived risks will positively and significantly correlate with each other. The results generally supported these hypotheses, and indicated that the unrealistic optimism process was employed quite consistently by the participating students.